O controle jurídico do desvio de finalidade legislativo: uma análise a partir da democracia representativa - Marques, Paulo Henrique Resende (2021)
This paper presents a robust rationale regarding the possibility of judicial control of the deviation of legislative purpose, a genus that encompasses, among its species, the purchase of votes from congressmen for the approval of law bills. For this, two theoretical bases are confronted, one resulting from the legal guarantee, by which the legislator's limitation would be in the material content of the Constitution, especially in fundamental rights. The other one derives from a proceduralist model, by which the violation of an ideal discursive model could lead to the illegitimacy of the law, since the intentions disclosed in the legislative debate are different from the real purposes of the issuer of the information. For the development of this research, a deductive method was used when carrying out the basis according to the respective major foundation premise, in order to, later on, contrast both positions, with no pretension of reaching the truth. As a result, this work was about rhetoric in order to seek the most appropriate argumentative support. Therefore, the hypothesis that such judicial control is not applicable is defended, due to the fact that, among other reasons, it is impossible to know for sure what led the congressman to vote in one direction, the feasibility of biased rules to serve the public interest and the preservation of legal security of acts produced by the Legislative Branch. In fact, the study separates the hypothesis of purpose deviation from others where there is no will, such as material error and coercion, showing that, in these cases, there may be consequences in relation to the validity of the legislative act produced, due to the absence of the volitional element. The relationship with the doctoral program of FDV (Law School of Vitória – ES), more specifically with the research line "Democracy, Citizenship and Fundamental Rights", is in the constitutional paradigm which tackles the violation, that is, the representative democracy. In addition to the doctrine on purpose deviation, legal guarantees, representative democracy and discourse theory, this paper is based on judgments by state courts that have examined the constitutionality of laws due to purpose deviation by the legislator, as well as judgments by the Federal Supreme Court on the discussed control, seeking to highlight the position of each minister, since there are differences between them on the purchase of legislative votes leading to unconstitutionality. This paper does not seek to defend acts originating from misconduct and corruption, but to preserve legal security and avoid the occurrence of such acts, for example, by punishing congressmen who perform them